2007
DOI: 10.1158/1055-9965.epi-06-0788
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor and Mammographic Density in Postmenopausal Norwegian Women

Abstract: Insulin-like growth factor-I (IGF-I) is associated with breast cancer risk among premenopausal women but rarely among postmenopausal women. Recent data from two European studies suggested an increased risk of breast cancer with increasing levels of IGF-I among women >50 years old or among postmenopausal hormone therapy users z55 years old. Mammographic density is one of the strongest risk factors, and possibly an intermediate marker, for breast cancer. We examined the relationship between IGF and mammographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 38 publications
2
37
1
Order By: Relevance
“…We have previously shown a positive association between plasma IGF-I concentrations and mammographic density in this study population. 24 Laboratory studies have suggested that IGF-I can both activate and increase the number of estrogen receptors, 20,21 and that the IGF-I-ER activation may be necessary for a maximal estrogen-mediated estrogen receptors activation. 21 In a case-control study among postmenopausal Chinese women, such a synergistic effect between estrone and IGF-I was suggested in relation to breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown a positive association between plasma IGF-I concentrations and mammographic density in this study population. 24 Laboratory studies have suggested that IGF-I can both activate and increase the number of estrogen receptors, 20,21 and that the IGF-I-ER activation may be necessary for a maximal estrogen-mediated estrogen receptors activation. 21 In a case-control study among postmenopausal Chinese women, such a synergistic effect between estrone and IGF-I was suggested in relation to breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…We kept these variables in the multivariate model along with the variables that previously have been found to be associated with mammographic density in this study population. 24,25,29 This procedure left the following factors to be included in the final model: age at screening, number of children, age at menopause, BMI and HT use.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a factor associated with mammographic breast density, the insulin-like growth factor (IGF) system has been well documented and reported to be of more relevance to premenopausal women (4,5). The IGF system acts as a factor controlling growth in the human body and plays an important role in the development of normal breast tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor-I (IGF-I), a circulating peptide, may be such a factor because its levels are associated with breast cancer risk (3) and it is mitogenic and inhibits apoptosis in breast epithelial cells (4). Despite this biologic plausibility, an association has not been observed between circulating IGF-I concentrations and percent dense area in most studies of postmenopausal women (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). As these studies were cross-sectional, how mammographic density changes as IGF-I levels change has not been examined.…”
Section: Introductionmentioning
confidence: 99%